2016
DOI: 10.1051/matecconf/20165904005
|View full text |Cite
|
Sign up to set email alerts
|

Copper Determination in Gunshot Residue by Cyclic Voltammetric and Inductive Coupled Plasma-Optical Emission Spectroscopy

Abstract: Abstract. Analysis of gunshot residue (GSR) is a crucial evidences for a forensic analyst in the fastest way. GSR analysis insists a suitable method provides a relatively simple, rapid and precise information on the spot at the crime scene. Therefore, the analysis of Cu(II) in GSR using cyclic voltammetry (CV) on screen printed carbon electrode (SPCE) is a better choice compared to previous alternative methods such as Inductive Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) those required a long time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Electrochemical methods were also used in a study by Hashim et al., in which they used cyclic voltammetry with a screen printed carbon electrode to detect Cu­(II) in GSR . They compared their results to those obtained using inductively coupled plasma optical emission spectroscopy (ICP-OES).…”
Section: Gunshot Residuementioning
confidence: 99%
“…Electrochemical methods were also used in a study by Hashim et al., in which they used cyclic voltammetry with a screen printed carbon electrode to detect Cu­(II) in GSR . They compared their results to those obtained using inductively coupled plasma optical emission spectroscopy (ICP-OES).…”
Section: Gunshot Residuementioning
confidence: 99%
“…It can tolerate constant mechanical stress without losing its attractiveness, a low-cost way for conducting onsite crime scene investigations in a range of forensic settings [143]. Hashim et al 2016 reported gold modified screen printed electrode for Cu (II) analysis in GSR using CV (Figure 9). It was also compared with ICP-OES analysis with 94% accuracy [144].…”
Section: Electrochemical Sensing In Forensicsmentioning
confidence: 99%